Clinical Implications of Serum Hypoxia Inducible Factor-1α and Vascular Endothelial Growth Factor in Lung Cancer. Issue 4 (July 2015) - Shen, Hong; Feng, Ganzhu; Cui, Jin; Du, Qiang; Qin, Yong; Cai, Jiankang; Shen, Li; Zhu, Yina
Aims and background: Hypoxia inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) have been deemed as key in angiogenesis of lung cancer. The aim of this study was to investigate diagnostic and prognostic values of HIF-1α and VEGF in patients with lung cancer. Methods: From May 1, 2011, to April 20, 2014, blood samples and/or pleural effusions were collected from 100 patients with lung cancer, 18 patients with tuberculosis, 47 patients with community-acquired pneumonia, and 29 healthy controls. The pretreatment levels of HIF-1α and VEGF were measured by enzyme-linked immunoassays. Patients with lung cancer were followed up during the period of this study and survival times were recorded for analysis. Results: We detected that the levels of serum and pleural HIF-1α in lung cancer were significantly higher than those in the tuberculosis population, and that the VEGF expressions were not significantly different between malignancy and benign diseases. An area under the curve of pleural HIF-1α (0.877 ± 0.053) showed a high ability to differentiate lung cancer from benign diseases. The significant negative predictors of survival in the univariate analysis were performance status (>1), no anticancer therapy, low serum albumin, advanced stage, and serum high level of VEGF (>324.17 pg/mL), while in the multivariate Cox regression analysis, only the pretreatment serum level of VEGF, stage, and anticancer therapy were identified as independent prognostic factors. Conclusions: The overexpression of HIF-1α especially in pleural effusion may be an angiogenic factor for distinguishing malignancy from tuberculosis, and the pretreatment level of serum VEGF may be an independent predictor of survival.